Identificacion y diferenciacion morfologica y molecular de Olpidium spp. - Herrera Vasquez, J.A.=700 1 Cebrian, M.C.; Fernandez, A.A.; Cordoba Selles, M.C.; Jorda, C.
(Es, En)
Ilus., 27 ref.
Keywords: OLPIDIUM; HONGOS; DIAGNOSTICO; IDENTIFICACION; MORFOLOGIA FUNGICA; ESPAÑA